2018
DOI: 10.3892/or.2018.6451
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of KPNA2 inhibits autophagy in oral squamous cell carcinoma cell lines by blocking p53 nuclear translocation

Abstract: Oral squamous cell carcinoma (OSCC), one of the 10 most common types of neoplasms in the US, constitutes ~90% of all cases of oral malignancies. Chemoresistance and metastasis are difficult to avoid during the course of treatment, leading to a poor prognosis and a high mortality rate for patients with OSCC. Autophagy, a critical conserved cellular process, has been reported to be highly associated with the regulation of chemoresistance and metastasis of cancer cells. The present study investigated the role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 66 publications
(70 reference statements)
1
17
0
Order By: Relevance
“…Apoptosis of Cal-27 cells is induced by KPNA2 through P53 in tongue squamous cell carcinoma [45]. Interaction between KPNA2 and P53 decreases autophagy of oral squamous cell carcinoma cells [46]. In the present study, WB detection revealed that the deletion of KPNA2 upregulated P53, P21, BAX, and cleaved-caspase3, and downregulated pro-caspase, BCL2, and CyclinD1, whereas the opposite results were found after overexpression of KPNA2.…”
Section: E921087-11supporting
confidence: 41%
“…Apoptosis of Cal-27 cells is induced by KPNA2 through P53 in tongue squamous cell carcinoma [45]. Interaction between KPNA2 and P53 decreases autophagy of oral squamous cell carcinoma cells [46]. In the present study, WB detection revealed that the deletion of KPNA2 upregulated P53, P21, BAX, and cleaved-caspase3, and downregulated pro-caspase, BCL2, and CyclinD1, whereas the opposite results were found after overexpression of KPNA2.…”
Section: E921087-11supporting
confidence: 41%
“…Yang et al 22 suggested knockdown of KPNA2 suppressed the prolifera- tion of HCC cells. Meanwhile, KPNA2 was also demonstrated to be associated with the proliferation of other human cancers including oral squamous cell carcinoma, 23 ovarian cancer, 24 colorectal cancer, 25 etc. Elevated expression of CDC20 was also demonstrated to be related with the development and progression of HCC, 26 and it was also associated with poor survival of others cancers like osteosarcoma, 27 breast cancer, 28 gastric cancer, 29 etc.…”
Section: Discussionmentioning
confidence: 99%
“…6F ). KPNA2 interacts with CAS during nuclear-cytoplasmic transport, and KPNA2 loss is associated with autophagy inhibition due to cytoplasmic accumulation of wild-type p53 [ 47 , 48 ]. In order to determine if PHY34 treatment changes p53 localization due to loss of KPNA2, we performed immunoblotting after nuclear-cytoplasmic fractionation.…”
Section: Resultsmentioning
confidence: 99%